PENGARUH PENERAPAN STRATEGI PEMBELAJARAN MURDER TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI SISWA KELAS X PASRAMAN KELAPA DUA - Wayan Mega Astini; Putu Jaya Adnyana W.; Ni Nyoman Sudiani (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2020)
This study aims to determine the influence of MURDER strategy on students ' learning outcomes in Hindu learning at Pasraman Purna Widya Kelapa Dua.This research is quantitative research with a semi-experimental design. To get results Pre test and Post Test from research conducted obtained test-T for Post Test class of 4.315 which shows that there is influence of the implementation of the MURDER strategy (Mood, Mood, Understand, Recall, Digest, Expand, and Review) on the outcome of learning Hindu education and ethics in the class X students Pasraman Kelapa Dua. Test-T for a pree test value of 0.29 which indicates both classes have the same ability. The average Post Test value for the experiment class is 89.75 and for the control class it is 85.4. While the average Pree Test value for the experimental class is 79.2 and for the control class is 79.6. From the research it can be concluded that the MURDER strategy can be used as an alternative to improve the learning outcomes of high school students in the Pasraman Kelapa Dua